App-based maintenance treatment for alcohol use disorder after acute inpatient treatment: Study protocol for a multicentre randomized controlled trial - Saur, Sebastian; Weisel, Kiona; Lang, Catharina; Fuhrmann, Lukas; Steins-Loeber, Sabine; Enewoldsen, Niklas; Reichl, Daniela; Zink, Mathias; Jakobi, Fabian; Rudolph, Melanie; Ahnert, Andreas; Braunwarth, Wolf Dietrich; et al. (Internet Interventions, 2022)
Background: Alcohol use disorder, a prevalent and disabling mental health problem, is often characterized by a chronic disease course. While effective inpatient and aftercare treatment options exist, the transferal of treatment success into everyday life is challenging and many patients remain without further assistance. App-based interventions with human guidance have great potential to support individuals after inpatient treatment, yet evidence on their efficacy remains scarce. Objectives: To develop an app-based intervention with human guidance and evaluate its usability, efficacy, and cost-effectiveness. Methods: Individuals with alcohol use disorder (DSM-5), aged 18 or higher, without history of schizophrenia, undergoing inpatient alcohol use disorder treatment (N = 356) were recruited in eight medical centres in Bavaria, Germany, between December 2019 and August 2021. Participants were randomized in a 1:1 ratio to either receive access to treatment as usual plus an app-based intervention with human guidance (intervention group) or access to treatment as usual plus app-based intervention after the active study phase (waitlist control/TAU group). Telephone-based assessments are conducted by diagnostic interviewers three and six weeks as well as three and six months after randomization. The primary outcome is the relapse risk during the six months after randomization assessed via the Timeline Follow-Back Interview. Secondary outcomes include intervention usage, uptake of aftercare treatments, AUD-related psychopathology, general psychopathology, and quality of life. Discussion: This study will provide further insights into the use of app-based interventions with human guidance as maintenance treatment in individuals with AUD. If shown to be efficacious, the intervention may improve AUD treatment by assisting individuals in maintaining inpatient treatment success after returning into their home setting. Due to the ubiquitous use of smartphones, the intervention has the potential to become part of routine AUD care in Germany and countries with similar healthcare systems.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Alcohol use disorder; App-based intervention; Germany; Human guidance; Maintenance treatment; RCT